PERTIMBANGAN HAKIM TERHADAP KETERANGAN AHLI AUDITOR DALAM PEMBUKTIAN PERKARA TIPIKOR (STUDI PUTUSAN NOMOR 84/PID.SUS-TPK/2023/PN BDG) - Aldini Pratiwi; Dara Pustika Sukma (Verstek, 2025)
This study aims to analyze the evidentiary strength of an auditor’s testimony as an expert witness in corruption trials and to evaluate whether the judge’s considerations in delivering the verdict align with the provisions of Article 183 of the Indonesian Criminal Procedure Code (KUHAP). The research adopts a normative legal approach with a case-based methodology, focusing on court verdict No. 84/Pid.Sus-TPK/2023/PN Bdg as the primary object of analysis. Legal materials used in this research include primary sources, such as statutes and court verdicts, and secondary sources, including books, journals, and articles. Legal material collection was conducted through library research, and the analysis employed a syllogistic deduction method. The findings reveal that the auditor’s testimony as an expert witness in corruption proceedings in Verdict No. 84/Pid.Sus-TPK/2023/PN Bdg holds legitimacy and significant evidentiary value in clarifying technical information regarding financial conditions relevant to corruption offenses. Furthermore, the judge’s considerations in issuing the verdict in the corruption case of Verdict No. 84/Pid.Sus-TPK/2023/PN Bdg adhere to the requirements of Article 183 of KUHAP, which mandates at least two valid pieces of evidence and the judge's conviction in ruling on a criminal case.